DESKRIPSI PENGETAHUAN SELF-CARE MANAGEMENT DALAM MENINGKATKAN KUALITAS HIDUP PADA PASIEN KANKER - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola; Ponda, Zabeli Syahbani (NURSE: Journal of Nursing and Health Science, 2025)
Background: According to the International Agency for Research on Cancer (IARC), there were 19.3 million new cases and nearly 10 million deaths due to cancer in 2020, where this condition is expected to continue to increase every year. The presence of cancer can affect a person's physical and psychological health conditions and influence their quality of life. Good self-management knowledge is very important for cancer patients to manage their health conditions independently and improve their quality of life. Objective: This study aims to determine the description of Self-Care Management Knowledge in improving the quality of life in cancer patients. Method: This descriptive analytical study was conducted on 90 cancer patients at the Achmad Mochtar Bukittinggi Hospital who were taken using accidental sampling techniques. This research instrument uses a self-management questionnaire based on the Nursing Outcomes Classification (NOC). Data analysis includes descriptive analysis to describe each statement found in the questionnaire. Results: The results showed that out of 90 respondents, more than half, namely 48 people (53.3%) of cancer patients had poor quality of life. Conclusion: Patients who have in-depth knowledge about their condition tend to feel more empowered and able to face the challenges posed by the disease. Thus, a deep understanding of the disease and the ability to manage symptoms effectively are essential for cancer patients in improving their quality of life. It is hoped that education on self-management should be carried out more often, because it plays an important role in improving the quality of life of cancer patients.